Analysis of Student Learning Motivation With Online Learning During the Covid-19 Pandemic - Nur Choiriyah Nur; Mustaji Mustaji (Buana Pendidikan, 2021)
Online learning as one of the impacts of the spread of the corona virus in the education sector must be implemented as an effort to maintain the implementation of education for the realization of the goals of national education. The implementation of online learning holding an important role, especially for students to achieve learning goals with all the impacts such as motivation and learning outcomes. This study is intended to describe the effect of implementing online learning during the Covid-19 pandemic on student learning motivation. This research is a quantitative study involving 254 respondents. The research instrument used a questionnaire in the form of questions packaged through the google form link to measure student motivation towards the implementation of online learning. The analysis of research results used simple linear regression testing equipped with normality tests and linearity tests as prerequisites. Based on the results of data analysis, the regression equation for student learning motivation towards online learning is Y = 16.911 + 0.573 X with t count of 10.574 and the coefficient of determination R2 = 0.307. These results indicate that the implementation of online learning has a positive influence on student learning motivation.